Program Initiative to Increase the Relevance of Islamic Religious Education in the Digital Era - Isnda yaa Dila; Juliani; Ade Lylyana; Calvin Apriando Ginting; Kati Zinger Wan Ranto (Journal of Contemporary Gender and Child Studies, 2024)
Islamic Religious Education (IRE) faces significant challenges in the rapidly evolving digital era. Information and communication technology not only influences students' mindsets and behaviors but also demands transformation in teaching approaches. This study aims to explore program initiatives that can enhance the relevance of IRE in the digital era through technology-based and pedagogical innovations. The research employs a qualitative approach using case study techniques conducted in several secondary schools in Indonesia. The findings reveal that the integration of technology into the curriculum, digital-based teacher training, and the development of interactive learning materials are strategic steps to address the challenges of the digital era. These findings provide practical guidance for educators and policymakers in designing relevant and effective IRE programs.